THE EFFECT OF ENTERPRISE RESOURCE PLANNING IN INCREASING FIRM’s VALUE - Deni Pandu Nugraha; Ervina Janis; Bisri Bisri (Universitas Muhammadiyah Kalimantan Timur, 2022)
This study analyzes the effect of Net Profit Margin, Total Asset Turnover, and Enterprise Resource Planning on firm’s value. And examine the influence of Enterprise Resource Planning in moderating Net Profit Margin and total asset turnover on a firm's value. The data used in this research is panel data. The sampling technique used was purposive sampling in totaling 23 state-owned companies listed on the Indonesian Stock Exchange for 2015-2019. The results showed that Net Profit Margin and Enterprise Resource Planning have a significant effect on firm value. Total Asset Turnover does not affect firm value. Enterprise Resource Planning is also unable to moderate the relationship between Net Profit Margin and firm value. Meanwhile, Enterprise Resource Planning moderate positively the relationship between total asset turnover and firm value.